Surgical Treatment of Peri-Implantitis Using a Combined Nd: YAG and Er: YAG Laser Approach: Investigation of Clinical and Bone Loss Biomarkers - Ioannis Fragkioudakis; Antonios Kallis; Evangelia Kesidou; Olympia Damianidou; Dimitra Sakellari; Ioannis Vouros (MDPI AG, 2023)
The current study aimed to investigate the effect of the combined Nd-Er: YAG laser on the surgical treatment of peri-implantitis by evaluating clinical markers and biomarkers of bone loss (RANKL/OPG). Twenty (20) patients having at least 1 implant diagnosed with peri-implantitis were randomly assigned to two groups for surgical treatment. In the test group (n = 10), Er: YAG laser was used for granulation tissue removal and implant surface decontamination, while Nd: YAG laser was employed for deep tissue decontamination and biomodulation. In the control group (n = 10), an access flap was applied, and mechanical instrumentation of the implant surface was performed by using titanium curettes. The following clinical parameters were evaluated at baseline and six months after treatment: Full-mouth Plaque Score (FMPS), Probing Pocket Depth (PPD), Probing Attachment Levels (PAL), recession (REC), and Bleeding on probing (BoP). Peri-implant crevicular fluid (PICF) was collected at baseline and six months for the evaluation of soluble RANKL and OPG utilizing enzyme-linked immunosorbent assay (ELISA). Baseline clinical values were similar for both groups, with no statistical differences between them. The study results indicated statistically significant improvements in the clinical parameters during the 6-month observation period in both groups. More specifically, PPD, PAL, and REC were improved in the test and control groups with no differences in the between-groups comparisons. However, a greater reduction in the BoP-positive sites was noted for the laser group (Mean change 22.05 ± 33.92 vs. 55.00 ± 30.48, p = 0.037). The baseline and six-month comparisons of sRANKL and OPG revealed no statistically significant differences between the two groups. The combined Nd: YAG-Er: YAG laser surgical therapy of peri-implantitis seemed to lead to more favorable improvements in regard to bleeding on probing six months after treatment compared to the conventional mechanical decontamination of the implant surface. None of the methods was found superior in the modification of bone loss biomarkers (RANKL, OPG) six months after treatment.